PENEGAKAN HUKUM TINDAK PIDANA MENGUBAH FUNGSI HUTAN MENJADI LAHAN PERKEBUNAN DI TAMAN NASIONAL TESSO NILO - Boby Dermawan Karo Karo; Zulfikar Jaya Kusuma; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Crime against forestry is a special criminal act regulated by criminalprovisions. Special criminal law is part of criminal law which is spread in variouslaws that are formed to regulate legal material specifically. Tesso Nilo NationalPark is a national park located in Riau province, Indonesia. Tesso Nilo NationalPark is a nature conservation forest area that has native ecosystems managed bya zoning system. The purpose of this paper is; firstly; to find out about the lawenforcement of forestry crime occurring in Teso Nilo National Park related to theconversion of forest land into plantations; second; to find out the problems offorestry crime that occur in Teso Nilo National Park; third; to find out theapplication of sanctions for legal provisions concerning forest conversionfunctions.This type of research can be classified as a type of sociological legalresearch, this research is descriptive, that is research that describes various factsand symptoms found in the Tesso Nilo National Park area for the activities ofconversion of protected forests. This research is a manifestation of researchresults regarding real or appropriate laws that live within the Tesso Nilo NationalPark area.From the results of research and discussion it can be concluded that,firstly; weak enforcement of forestry criminal law against perpetrators of forestconversion into plantation land; second; It is difficult to prosecute actorsinvolved, both directly and indirectly in plantation activities in protected forests.Keywords: Forestry Crime-Law Enforcement-Sanctions